ChemInform Abstract: A General Protocol for the Efficient Synthesis of Polyarylated Benzenes by Multiple Suzuki‐Miyaura Reactions of Polychlorinated Benzenes. Issue 24 (27th May 2016) - Reimann, Sebastian; Ehlers, Peter; Sharif, Muhammad; Spannenberg, Anke; Langer, Peter
Abstract: A highly efficient and simple protocol for the synthesis of multiarylated benzenes by palladium‐catalyzed Suzuki‐Miyaura reaction of chlorobenzenes is presented.